DIVERSITY OF AMINO ACIDS COMPOSITION IN CEREALS: Amino acids in cereals - Tomičić, Zorica; Spasevski, Nedeljka; Lazarević, Jasmina; Čabarkapa, Ivana; Tomičić, Ružica (Food and Feed Research, 2022)
The quality of protein is based on their amino acid composition, especially on the content and availability of essential amino acids. Cereals are important sources of protein for human nutrition, but are limited in the amounts of essential amino acids, notably lysine. The aim of this study was to analyse the chemical composition and amino acid profiles of different cereals that are important for nutritional purposes in human diet.  The content of protein, moisture and crude fat in cereals varied significantly from 7.83 to 13.22 %, 11.45 to 13.80 %, and from 1.67 to 6.35 %, respectively. Obtained results showed that oat had the highest contents of crude protein (13.22 %), crude fat (6.35 %) and crude cellulose (9.42 %) compared to other cereals. Significant (p < 0.05) variation existed in the content of essential and nonessential amino acids among samples with the highest level in oat and wheat. Concerning the proportion of essential amino acids in total amino acids could be concluded that made one third in the tested cereals. Glutamic acid was found to be the most abundant amino acid. It could be concluded that the amino acid composition of oat is the most favourable among cereals due to its high protein content and the content of lysine which can be found in limited amounts in the most cereals.
Keywords: essential amino acids; non-essential amino acids; chemical composition; nutritional profile; dietary reference intake